2023
DOI: 10.3389/fvets.2022.1089999
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of different tick species on livestock and associated equines and canine from different agro-ecological zones of Pakistan

Abstract: Ticks are ectoparasites that act as vectors for transmission of various pathogens to wild and domesticated animals and pose a serious threat to human health. Because of the hot and humid conditions in different agro-ecological zones of Pakistan, ticks are abundant and parasitize a variety of animals. The aim of this study was to identify different tick species and distribution on different hosts especially livestock, such as sheep, goat, cattle, buffalo, and camel, and livestock associated canines and equines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…It has been reported that about 1 million deaths are observed annually due to tick-borne pathogens (WHO, 2014 ). Ticks are an immense source of spreading zoonotic diseases such as tularemia, tick-borne relapsing fever, Rocky Mountain spotted fever, anaplasmosis, and ehrlichiosis (Bratton and Corey, 2005 ; Hussain N. et al, 2023 ). Developing countries like tropical and subtropical countries are in consensus due to TBDs exerting economic challenges on the worldwide livestock sector.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that about 1 million deaths are observed annually due to tick-borne pathogens (WHO, 2014 ). Ticks are an immense source of spreading zoonotic diseases such as tularemia, tick-borne relapsing fever, Rocky Mountain spotted fever, anaplasmosis, and ehrlichiosis (Bratton and Corey, 2005 ; Hussain N. et al, 2023 ). Developing countries like tropical and subtropical countries are in consensus due to TBDs exerting economic challenges on the worldwide livestock sector.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of small ruminants to the rural economy the production by these animals is not as efficient as it should be [ 5 ]. Due to the subtropical conditions in Pakistan, ticks and associated tick-borne diseases are abundant in domesticated animals, especially in the arid regions of Punjab with higher temperatures and humidity during most part pf the year [ 6 ]. Ticks and their transmitted pathogens cause weight loss, skin damage, mortality and abortion resulting in huge annual economic losses [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ticks of genus Hyalomma are vectors for the Crimean-Congo hemorrhagic fever (CCHF), a serious threat endemic in Pakistan [8]. To date, 27 species of Hyalomma have been identified in Palearctic, Oriental, and African regions [9], of which 13 have been reported in Pakistan [2,[10][11][12][13][14][15]. The genus Hyalomma has been classified into two subgenera, i.e., Euhyalomma and Hyalommina.…”
Section: Introductionmentioning
confidence: 99%
“…Pakistan has a huge population of small ruminants that consists of approximately 78.2 million goats and 31.2 million sheep [19]. The list of Hyalomma ticks infesting small ruminants in Pakistan includes Hyalomma anatolicum, Hyalomma dromedarii, Hyalomma isaaci, Hyalomma hussaini, Hyalomma scupense, Hyalomma asiaticum, Hyalomma kumari, and Hyalomma turanicum [2,12,13,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%